Effect of Agroforestry and Natural Forest on Air Surface Temperature in Eastern Phi in Pan Nam Mountain Range Area, Thailand - Podong, Chattanong; Kaiyuttinun, Parinya; Peerapak, Wanwisa (Science Essence Journal, 2021)
In this study, the air surface temperature variation in the agroforestry and natural forest areas in Eastern Phi Pan Nam mountain range, Uttaradit Province was studied by selecting the plant communities in a traditional agroforestry in Mae Phun Subdistrict, Laplae District (LP-AF), an applied agroforestry in Ban Dan Na Kham Subdistrict, Mueang Uttaradit District (DK-AF), and a developed agroforestry in Nang Phaya Subdistrict, Tha Pla District, Uttaradit Province (NP-AF), as well as two natural forest areas in Eastern Phi Pan Nam mountain range, Uttaradit Province which were a mixed deciduous forest (LN-NF) and a hill evergreen forest (PP-NF) in Lamnam Nan National Park, Uttaradit Province in order to establish the sample plots and install the automatic weather stations for recording the average daily temperature over a period of 10 months. According to the results, the lowest average temperature of 37.32 °C was observed in the traditional agroforestry in Mae Phun Subdistrict, Laplae District (LP-AF) and the average air surface temperature of the applied agroforestry in Ban Dan Na Kham Subdistrict, Mueang Uttaradit District (DK-AF) was 28.30 °C which was 0.98 °C higher compared to that of the agroforestry in Mae Phun Subdistrict, Laplae District (LP-AF). In addition, it was found that the average air surface temperature of the agroforestry in Nang Phaya Subdistrict, Tha Pla District, Uttaradit Province (NP-AF) was 28.07 °C which was 0.75 ° higher compared to that of the agroforestry in Mae Phun Subdistrict, Laplae District (LP-AF). Compared to the natural forest areas, all these 3 agroforestry systems showed no difference in the average air surface temperature compared to the mixed deciduous forest. However, significant difference was observed when all these 3 agroforestry systems were compared to the hill evergreen forest at a confidence level of 95%.